Managing innovation as a self-renewing process - Nonaka, Ikujiro; Yamanouchi, Teruo (Journal of Business Venturing, 1989)
In order to remain competitive, a firm must constantly create new strategies, products and features as well as new ways of manufacturing, promoting and distributing its products. The process of new product development can serve as a catalyst for the self-renewal of an organization. Developing a new product forces members of an organization to create innovative approaches to problems which may then lead to shifts in the thinking of the firm. Most studies have regarded the organization as a machine for information processing. However, a view in which humans are likened to parts of a machine overlooks a very important aspect in considering the process of organizational self-renewal. Although humans have a finite ability to process information, they also have the ability to create information by looking at things in a new way or adopting a different point of view. This change in thinking can lead to a new awareness throughout the organization, and can help to solve the problems which seem to have no traditional solution. Information which arises in this process competes with and complements other information in the organization. Eventually, the new and the existing information may be integrated to produce a change in organizational cognitive and behavioral patterns. This results in the self-renewal of the organization. This study examines the process of new product development through a case study of the creation of the Canon personal copier, and outlines a series of stages for promoting innovation and organizational self-renewal. The analysis of the process used by Canon in creating the personal copier indicates that the self-renewal of the firm may result from deliberately creating a climate of turbulence and constructive conflict within the organization. In such an environment, dynamic cooperation between different divisions or task forces is encouraged and new solutions to complex problems are found. The viewpoint presented in this study—that the self—renewal of an organization is a process of information creation-could be extended to create new theoretical frameworks. While Canon's approach to fostering information creation was effective, however, other methods of organizational self-renewal should be explored.